Warming climate extends dryness-controlled areas of terrestrial carbon sequestration - Yi, Chuixiang; Wei, Suhua; Hendrey, George (Scientific reports, 2014)
At biome-scale, terrestrial carbon uptake is controlled mainly by weather variability. Observational data from a global monitoring network indicate that the sensitivity of terrestrial carbon sequestration to mean annual temperature ( T ) breaks down at a threshold value of 16°C, above which terrestrial CO 2 fluxes are controlled by dryness rather than temperature. Here we show that since 1948 warming climate has moved the 16°C T latitudinal belt poleward. Land surface area with T > 16°C and now subject to dryness control rather than temperature as the regulator of carbon uptake has increased by 6% and is expected to increase by at least another 8% by 2050. Most of the land area subjected to this warming is arid or semiarid with ecosystems that are highly vulnerable to drought and land degradation. In areas now dryness-controlled, net carbon uptake is ~27% lower than in areas in which both temperature and dryness ( T < 16°C) regulate plant productivity. This warming-induced extension of dryness-controlled areas may be triggering a positive feedback accelerating global warming. Continued increases in land area with T > 16°C has implications not only for positive feedback on climate change, but also for ecosystem integrity and land cover, particularly for pastoral populations in marginal lands.